PENERAPAN MODEL RADEC MENGGUNAKAN MEDIA NEARPOD UNTUK MENINGKATKAN LITERASI BUDAYA DAN KEWARGANEGARAAN DI SDN CIBENING 01 PAMIJAHAN BOGOR - Suryadi, Ainun; Lestari, Hana; Rahmawati, Ima (Prodi PGMI IAI Sahid, 2026)
Cultural and civic literacy is a person's skill in having a personality in a community environment which is part of a national culture so that they can always be proud and always preserve the culture of the Indonesian nation. This study aims to determine the application of the RADEC learning model to improve students' cultural and civic literacy. The method used is a pre-experiment with a one-group pretest posttest design. This study was conducted on grade V students of SDN Cibening 01, Pamijahan District, Bogor. The sample in this study used non-prpbability sampling with a sample size of 41 students. The instruments used were tests of students' cultural and civic literacy skills and observation sheets. The cultural and civic literacy skills test was carried out in two stages, namely pretest and posttest. from the study, the average value of students' cultural and civic literacy skills in the pretest was 55.37, while the average posttest value was 71.59. Data processing was analyzed using SPSS 21 for windows with Paired Sample t-test at α (0.001) and obtained a sig value of 0.000 <α (0.001). The results showed that there was a significant difference between the pretest and posttest. It can be interpreted that there is an increase in students' cultural and citizenship literacy skills before and after the implementation of the RADEC model using nearpod learning media.